Woman’s Labor Participation and Household Welfare: An Empirical Study in Sumatera Island - Nopiah, Ririn; Anggraini, Eka Dewi; Islami, Puji Amalia (Universitas Gadjah Mada, 2024)
Household consumption pattern has been used as an indicator for measuring the level of household welfare in Indonesia. The availability of labor in formal or informal sector is needed by the society to fulfill household needs. This is especially the case with informal sector thatstill dominates higher in Indonesia because this sector is a widely open alternative for the society in Indonesia. However, it often overlooked that the welfare of these jobs affects the transmission mechanism of intra-household job allocation, including women workers. This studyanalyzes women’s labor participation in the formal and informal sectors on household welfare on Sumatra Island. The method of this research is based on analysis of the data of Indonesia family Survey (IFL 5) in 2014. This data provided by the Indonesian Central Bureau of Statisticsor Badan Pusat Statistik (BPS) offers a longitudinal on household in Indonesia. This research use sample of 2.610 household The data is analysed using Two Stage Least Square (2SLS) through variable instruments (IV). The results show that women household heads who work in the informal sector have a higher welfare than the formal sector and women household heads whoare widowed tend to have low welfare. The regional government is expected to be able to maximize human development policies to reduce the gaps of household welfare based on gender, especially for women.